In Vitro Resistance Selection in Shigella flexneri by Azithromycin, Ceftriaxone, Ciprofloxacin, Levofloxacin, and Moxifloxacin - Allen, George P. (Antimicrob Agents Chemother, 2017)
Shigella flexneri continues to be a major cause of diarrhea-associated illness, and increasing resistance to first-line antimicrobials complicates the treatment of infections caused by this pathogen. We investigated the pharmacodynamics of current antimicrobial treatments for shigellosis to determine the likelihood of resistance promotion with continued global antimicrobial use. The mutant prevention concentration (MPC) and mutant selection window (MSW) were determined for azithromycin, ceftriaxone, ciprofloxacin, levofloxacin, and moxifloxacin against a wild-type strain of S. flexneri (ATCC 12022) and an isogenic gyrA mutant (m-12022). Time-kill assays were performed to determine antimicrobial killing. Concentrations of approved doses of ciprofloxacin, levofloxacin, and moxifloxacin are predicted to surpass the MPC for a majority of the dosage interval against ATCC 12022. However, against m-12022, concentrations of all fluoroquinolones are predicted to fall below the MPC and remain in the MSW for a majority of the dosage interval. Concentrations of ceftriaxone fall within the MSW for the majority of the dosage interval for both strains. All agents other than azithromycin displayed bactericidal activity in time-kill assays. Results of pharmacodynamic analyses suggest that all tested fluoroquinolones would achieve a favorable area under the concentration-time curve (AUC)/MPC ratio for ATCC 12022 and would restrict selective enrichment of mutants but that mutant selection in m-12022 would be likely if ciprofloxacin were used. Based on pharmacodynamic analyses, azithromycin and ceftriaxone are predicted to promote mutant selection in both strains. Confirmation of these findings and examination of novel treatment regimens using in vivo studies are warranted.